2004
DOI: 10.1029/2003jb002407
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave attenuation and dispersion in melt‐bearing olivine polycrystals: 2. Microstructural interpretation and seismological implications

Abstract: [1] The torsional forced oscillation tests of melt-bearing olivine aggregates reported by Jackson et al. [2004] consistently show a peak in attenuation that is absent from melt-free aggregates tested under similar conditions and grain sizes. Characterization by SEM shows that the melt resides in triple junction tubules and larger pockets as previously described. TEM imaging and EDS analysis reveals that olivine-olivine grain boundaries are characterized by a region 1 nm wide which is structurally and chemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
172
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 52 publications
14
172
1
2
Order By: Relevance
“…Seismic attenuation in the upper mantle is thought to occur through two potential mechanisms: grain boundary sliding (Faul et al, 2004) and melt squirt (Mavko and Nur, 1975;O'Connell and Budiansky, 1977). Grain boundary sliding has been shown to cause a broad absorption peak in the seismic frequency band and so cannot explain the low attenuation that we observe (Faul et al, 2004). Hammond and Humphreys (2000) modeled the effect that melt squirt has on attenuation in the upper mantle with melt percentages ranging from 0% to 3%.…”
Section: Discussionmentioning
confidence: 87%
“…Seismic attenuation in the upper mantle is thought to occur through two potential mechanisms: grain boundary sliding (Faul et al, 2004) and melt squirt (Mavko and Nur, 1975;O'Connell and Budiansky, 1977). Grain boundary sliding has been shown to cause a broad absorption peak in the seismic frequency band and so cannot explain the low attenuation that we observe (Faul et al, 2004). Hammond and Humphreys (2000) modeled the effect that melt squirt has on attenuation in the upper mantle with melt percentages ranging from 0% to 3%.…”
Section: Discussionmentioning
confidence: 87%
“…For example, an $2.5% shear wave velocity decrement per 1% melt volume is commonly reported [Hier-Majumder and Courtier, 2011; Kreutzmann et al, 2004;Takei, 2000] while Hammond and Humphreys [2000] found velocity reductions in excess of 7.9% per 1% melt. The effect of melt on seismic attenuation is also unclear [Faul et al, 2004;Gribb and Cooper, 2000]. Surface and body-wave tomography results suggest that most of the upper mantle velocity variation in the western United States, including the CRM, can be largely attributed to temperature differences [Goes and van der Lee, 2002;Schmandt and Humphreys, 2010].…”
Section: Mantle Temperaturementioning
confidence: 99%
“…In this paper we exclude features such as melts on interfaces and refer to Hiraga et al (2002) for intergranular melt phases with a characteristic thickness in the range of 0.5-10 nm and de Kloe et al (2000), Tan et al (2001) and Faul and Jackson (2004) for careful analysis of meltbearing systems involving olivine. While it is possible to extract information about the melt, we focus here on meltfree interfaces without grain boundary sliding or any other movement which trivially leads to dissipation of strain energy.…”
Section: Introductionmentioning
confidence: 99%